Bound to Fail? Exploring the Systemic Pathologies of CSR and Their Implications for CSR Research. Issue 7 (September 2020) - Schneider, Anselm
Among critics of corporate social responsibility (CSR), there is growing concern that CSR is largely ineffective as a corrective to the shortcomings of capitalism, namely, the negative effects of business on society and the undersupply of public goods. At the same time, researchers suggest that despite the shortcomings of CSR, it is possible to make it more effective in a stepwise manner. To explain the frequent failures of current CSR practices and to explore the possibilities of remedying them, I examine the close relationship between CSR, the persistent expansion of capitalism, and the pressure that capitalism puts on companies to legitimize their business operations. My analysis shows that the failure of CSR to serve as a corrective to the problematic effects of capitalism is, in fact, an inevitable consequence of the problematic dynamics of the capitalist system. On this basis, I suggest that capitalism limits the possibilities of making CSR more effective, argue for change on the systemic level of capitalism, and explore the ways in which CSR research can contribute to this political endeavor.